Polyaniline- and poly(ethylenedioxythiophene)-cellulose nanocomposite electrodes for supercapacitors - Liew, Soon Yee; Thielemans, Wim; Walsh, Darren A. (Springer Verlag, 2014)
The formation and characterisation of films of polyaniline (PANI) and poly(ethylenedioxythiophene) (PEDOT) containing cellulose nanocrystals (CNXLs) from cotton are described. PANI/CNXL films were electrodeposited from a solution containing CNXLs, HCl and aniline, while PEDOT/CNXL films were electrodeposited from a solution containing CNXLs, lithium perchlorate and ethylenedioxythiophene. In each case, incorporation of CNXLs into the electrodepositing polymer film led to the formation of a porous polymer/CNXL nanocomposite structure. The films were characterised using scanning electron microscopy, cyclic voltammetry, electrochemical impedance spectroscopy (EIS) and galvanostatic charge-discharge analysis. The specific capacitances of the nanocomposite materials were higher than those of the CNXL-free counterparts (488 F/g for PANI/CNXL; 358 F/g for PANI; 69 F/g for PEDOT/CNXL; 58 F/g for PEDOT). The durability of the PANI/CNXL film under potential cycling was slightly better than that of the CNXL-free PANI, while the PEDOT film was slightly more durable than the PEDOT/CNXL film. Using electrodeposition, it was possible to form thick PANI/CNXL films, with total electrode capacitances of 2.07 F farads per squared cm (and corresponding specific capacitances of 440 F/g), demonstrating that this particular nanocomposite may be promising for the construction of high performance supercapacitors.